Methodological characteristics, physiological and physical effects, and future directions for velocity-based training in soccer: A systematic review - Ribeiro, J.; Afonso, J.; Camoes, M.; Sarmento, H.; Sa, M.; Lima, R.; Clemente, F. M. (Baltic Journal of Health and Physical Activity, 2022)
Introduction: Although soccer matches require players to perform repetitive power-related abilities, the impact of lower-body strength and Introduction. This systematic review was conducted to (1) characterize the main elements of studies of velocity-based training (VBT) (e.g., training protocols) conducted in soccer, (2) summarize the main physiological and physical effects of VBT on soccer players, and (3) provide future directions for research. Methods: A systematic review of Cochrane Library, EBSCO, PubMed, Scielo, Scopus, SPORTDiscus, and Web of Science databases was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: The database search initially identified 127 titles. Of those, five articles were deemed eligible for the systematic review, two studies used a traditional strength training approach, and the other remaining three used sprint training with either resisted sprints or combined resisted and unresisted sprints. All studies addressed strength and power and sprint outcomes, three measured jump performance improvements, and only one study addressed spatiotemporal and kinematics or aerobic measures regarding adaptations to VBT interventions. Only one study addressed acute responses to VBT training regarding spatiotemporal variables and kinematics. Conclusions: Acute responses to VBT training were as follows: when sprint time decreases by at least 50-60%, sprint kinematics are immediately affected, but spatiotemporal variables are only significantly affected when velocity loss (v.loss) reaches at least 60%. For long-term adaptations, it seems that for strength increases using the squat, higher or lower velocity loss due to in-set fatigue accumulation does not make a difference, although it does affect jump performance, favoring the low v.loss groups (15%). The same applies to sprint, as low v.loss accumulation due to fatigue along sets seems to be detrimental to sprint performance adaptations. Moreover, high v.loss during sprints due to external load can improve sprint performance without harming the running technique as was previously thought.